2007
DOI: 10.1373/clinchem.2006.076711
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Dimethylarginine Independently Predicts Total and Cardiovascular Mortality in Individuals with Angiographic Coronary Artery Disease (The Ludwigshafen Risk and Cardiovascular Health Study)

Abstract: Background: Asymmetrical dimethylarginine (ADMA) is increased in conditions associated with increased risk of atherosclerosis. We investigated the use of ADMA to predict total and cardiovascular mortality in patients scheduled for coronary angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
126
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(144 citation statements)
references
References 51 publications
13
126
1
4
Order By: Relevance
“…Evidence for an association between high blood pressure and elevated ADMA levels comes from small clinical studies (29,35). Other reports, including several large-scale clinical studies, did not confirm such an association (25,31). Our blood pressure results are limited because we only used a noninvasive tail-cuff method, a technique that has received criticism in the past.…”
Section: Discussionmentioning
confidence: 80%
“…Evidence for an association between high blood pressure and elevated ADMA levels comes from small clinical studies (29,35). Other reports, including several large-scale clinical studies, did not confirm such an association (25,31). Our blood pressure results are limited because we only used a noninvasive tail-cuff method, a technique that has received criticism in the past.…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have shown that plasma ADMA level may predict the progression of renal injury in patients with early-stage CKD (12,13). In addition, high plasma ADMA level has been reported to be an independent risk factor for cardiovascular disease and allcause mortality in a community-based population (14), in patients with coronary artery disease (CAD) (15,16), and in patients with ESRD (17,18). However, evidence about the association between ADMA and patients with mild to moderate CKD is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, ADMA concentrations are higher in dialysis patients with clinically manifest atherosclerosis than in those without atherosclerotic disease (17), which suggests that accumulation of ADMA might be an important cardiovascular risk factor in end-stage renal disease. Moreover, the clinical importance of ADMA in coronary artery disease is highlighted in a recent trial by Meinitzer et al (18) in which ADMA predicted cardiovascular events in 3200 patients. In addition, ADMA predicts coronary events in middle-aged white men (19).…”
mentioning
confidence: 99%